The Effect of Individual-Made Insole on Standing Balance in Students with Flexible Flat Feet (Pilot Study) - พุ่มสุทัศน์, ผกาวลี; แสงนนท์, ชไมพร; กิ่งไทยสงค์, ปริญญาภรณ์; ฝังเงิน, วรรณา; หิรัญสถิต, สุจิตรา (Journal of health and health management, 2019)
Flat feet are the condition which Medial Longitudinal Arch (MLA) of feet collapses. The prevalence of flat feet in healthy adult aged 18-21 years is 13.6%. Flat feet results more weight bearing in medial side of feet during standing, walking, or running which influences on activity daily living. The objective of this study was to study the effect of insole on balance of volunteer with flexible flat feet. The samples were fifteen volunteers aged 18-25 years (21+1.2 years) with flexible flat feet, BMI ≤ 22.9 kg/m2, BESS score > 5 were recruited. The simple sampling was used to divide insole group and no insole group. 8 volunteers in insole group had insole shoes for 3 weeks. 7 volunteers in no insole group had no insole shoes. BESS score was measured at beginning of 1st week and the end of 3rd week in both group. Data analysis pre average BESS and 3rd average BESS in each group were analyzed by Dependent t-test. Pre average BESS and 3rd average BESS between groups were analyzed by Independent t-test at p-value ≤0.05. The results indicated that the comparison of 3rd average BESS score between insole group (5.25±1.04) and no-insole group (7.14±1.07) showed significance differences (P≤0.05). Conclusion: Volunteers with individual invented insole shoes for 3 weeks had average BESS significant better than volunteers with no-insole shoes (P≤0.05).